Dinamika Kepemimpinan Partisipatif dalam Mengatasi Fragmentasi Sosial di Pesantren - Husnul Khotimah (Visionaria: Journal of Educational Innovation Management, 2025)
Social fragmentation within organizations often emerges as a consequence of unmanaged cultural and value-based heterogeneity, leading to polarization that undermines internal cohesion. This study aims to explore the dynamics of participatory leadership as a transformative strategy for mitigating social fragmentation, particularly within Islamic boarding schools (pesantren), which are marked by complex social structures and deeply rooted value systems. Employing a qualitative approach with a case study design, the research engages administrators and students (santri) who are actively involved in navigating fragmented social environments. Data were collected through in- depth interviews, participatory observation, and institutional document analysis, and subsequently analyzed using a thematic- constructivist framework to uncover patterns of meaning and social practice. The findings indicate that participatory leadership significantly contributes to social reconciliation by facilitating intergroup interaction, creating inclusive dialogue spaces, and fostering trust-based social capital. This approach has proven adaptive in addressing internal diversity and effective in managing social tension through deliberative engagement. Beyond highlighting the normative dimensions of value-based leadership, the study offers both conceptual and practical contributions to the development of inclusive leadership strategies in Islamic educational institutions. Overall, the findings emphasize the urgency of policy formulation and capacity building for organizational leaders to construct a just, integrative, and resilient social ecosystem.